O Papel o Intérprete de Libras no Contexto da Educação Inclusiva: Problematizando a Política e a Prática. - Araújo, Joelma Remigio de (2011)
This is a qualitative ethnographic study about inclusive educational policies for deaf people regarding the presence of Sign Language Interpreters (SLI) in the school environment. We chose to deal with this subject because we understand that this professional is of vital importance to the education of deaf people, taking also into consideration the historical moment in which the profession was recognized by a specific law. Therefore, accepting that the performance of this professional is becoming increasingly more important, we aimed at observing how the interpreter is carrying out his/her job in inclusive schools and what consequences his/her performance has in the schooling of deaf people. The research was conducted in five state schools - two middle schools (Brazilian fundamental II level) and three high schools (Brazilian secondary school) -, which had Sign Language Interpreters facilitating communication in the classrooms. Observations of the performance of thirteen SLI were carried out for three months, because this professional is, according to Quadros (2004), the one responsible for the interpretation of one language (source language) into another (target language), in this specific case from Portuguese into (Brazilian) Sign Language and vice versa. Based upon the existing legal recommendations on this professional and his/her performance, we found out that in the classrooms of the schools participating in the research this interpretation did not happen as it should in many situations. Even though the presence of this professional has already been a reality for some years in state schools, many issues concerning his/her performance need to be reviewed and reevaluated. There have not been enough and necessary training programs to support the practices of those SLI already working at state schools, and perhaps this accounts for the misunderstanding between the teacher s and interpreter s roles, which causes conflicts of pedagogical knowledge and roles. Considering the interviews conducted, we can also point out that, out of the 13 SLI who participated in this study, just a few of them are aware of the historical facts associated with deaf people s education, and there are no opportunities for them to take part in the planning process with teachers. When comparing what was said and what was actually done in the classrooms, we noticed that some of the practices observed do not match what was mentioned in the interviews with regard to SLI s performance and presence in the school environment. Therefore, the reality observed indicated an urgent need for the establishment of criteria for hiring SLI who will work at the schools, as well as the promotion of qualification courses for those who are already working or intend to work as interpreters in the educational environment.